2007
DOI: 10.1007/s10489-007-0069-8
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive evolutionary algorithm with intelligent mutation local searchers for designing multidrug therapies for HIV

Abstract: This paper proposes a novel Memetic Algorithm consisting of an Adaptive Evolutionary Algorithm (AEA) with three Intelligent Mutation Local Searchers (IMLSs) for designing optimal multidrug Structured Treatment Interruption (STI) therapies for Human Immunodeficiency Virus (HIV) infection. The AEA is an evolutionary algorithm with a dynamic parameter setting. The adaptive use of the local searchers helps the evolutionary process in the search of a global optimum. The adaptive rule is based on a phenotypical dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 50 publications
0
42
0
Order By: Relevance
“…We introduce a population index ξ [26] in order to measure its diversity and it can be calculated as follows:…”
Section: Statistics Based Learning Behaviormentioning
confidence: 99%
“…We introduce a population index ξ [26] in order to measure its diversity and it can be calculated as follows:…”
Section: Statistics Based Learning Behaviormentioning
confidence: 99%
“…where A(q), B(q) and C(q) are given as the ARMAX model polynomial over q, y(k) is given as the output variable of the model, u(k) is given as the control variable, n(k) is given as the uncorrelated white noise with zero mean, e(k) is also given as the error modeling and finally (k) is given as the model parameters adaptation [34][35][36]. As it can be seen from the proposed strategy, the linear generalized predictive control; LGPC, scheme is used as controller of the system.…”
Section: The Proposed Multiple Models Strategymentioning
confidence: 99%
“…Some researchers [15,23] have suggested that multiple LS operators should be executed simultaneously on those individuals that are selected for local improvements and that a certain learning mechanism should be adopted to give the efficient LS methods greater chances to be chosen in the later stage. However, Neri et al [22] have also proposed a multiple LS based MA with a non-competitive scheme, where different LS methods can be activated during different population evolution periods. Inspired by these researches, an adaptive hill climbing (AHC) strategy that hybridizes the GCHC and SMHC methods described in Section 2.2 is proposed in this paper.…”
Section: Adaptive Hill Climbing (Ahc)mentioning
confidence: 99%